Virulence‐targeted Antibacterials: Concept, Promise, and Susceptibility to Resistance Mechanisms. (6th February 2015) - Ruer, Ségolène; Pinotsis, Nikos; Steadman, David; Waksman, Gabriel; Remaut, Han
<x xml:space="preserve">Abstract</x> In view of the relentless increase in antibiotic resistance in human pathogens, efforts are needed to safeguard our future therapeutic options against infectious diseases. In addition to regulatory changes in our antibiotic use, this will have to include the development of new therapeutic compounds. One area that has received growing attention in recent years is the possibility to treat or prevent infections by targeting the virulence mechanisms that render bacteria pathogenic. Antivirulence targets include bacterial adherence, secretion of toxic effector molecules, bacterial persistence through biofilm formation, quorum sensing and immune evasion. Effective small‐molecule compounds have already been identified that suppress such processes. In this review, we discuss the susceptibility of such compounds to the development of resistance, by comparison with known resistance mechanisms observed for classical bacteriostatic or bacteriolytic antibiotics, and by review of available experimental case studies. Unfortunately, appearance of resistance mechanisms has already been demonstrated for some, showing that the quest of new, lasting drugs remains complicated.